Pendampingan Studi Kelayakan untuk Pengembangan Lanjut Aplikasi Math-MBC di Yayasan Mitra Netra - Kelana, Bayu; Arapenta Sembiring, Albert (Indonesian Journal for Social Responsibility, 2024)
The Mitra Netra Foundation wishes to continue the development of the existing Math Mitra Netra Braille Converter (Math-MBC) application based on several new requirements. This application can convert mathematical formulas from regular format to Braille format or vice versa. It can help visually impaired students and educators who are not familiar with Braille to conduct mathematics learning activities. The Mitra Netra Foundation needs assistance from other parties to realize its goal, including conducting a feasibility study as the initial stage of further development. This community service activity aims to assist the Mitra Netra Foundation in conducting a feasibility study for the further development of the Math-MBC application. Therefore, this activity is carried out over two months with two participants experienced in the field of assistive technology development for the visually impaired at the Mitra Netra Foundation. This activity consists of two stages: introducing the Technical, Economic, Legal, Operational, and Scheduling (TELOS) method and assisting in the feasibility study. Using the TELOS method, the feasibility study of the application development is conducted from technical, economic, legal, operational, and scheduling aspects. Based on the analysis, further development is feasible if done by another party, funded by a grant, within a minimum period of four months. The Mitra Netra Foundation is satisfied with the benefits, materials, organization, and time efficiency of this activity. This activity has provided the participants with new understanding in conducting feasibility studies for application development in the future. It also resulted in a feasibility study document for the further development of the Math-MBC application. This document can serve as a reference for the Mitra Netra Foundation to take the next steps in further developing the Math-MBC application.